Speech by the Honourable Chief Minister Penang at the National Annual Dinner of the Australian and New Zealand Graduates Association of Malaya to be held at Pago Pago Lounge Hotel Merlin on Saturday 2nd October 1976 at 7.30 p.m. - Lim, Chong Eu (1976)
I deem it a great honour to have been invite by the members of the Australian and New Zealand Graduates Association of Malaya to be present and to address you on this happy occasion of your National Annual Dinner.